Nutrient status in coral reefs of the Îles Eparses (Scattered Islands): comparison to nearby reefs subject to higher anthropogenic influences (Mozambique Channel and Mascarenes, Indian Ocean) - Riaux-Gobin, Catherine; Witkowski, Andrzej; Saenz-Agudelo, Pablo; Neveux, Jacques; Oriol, Louise; Vétion, Gilles (Oceanological and hydrobiological studies, 2011)
Indian Ocean coral reef environments off Mascarenes (Réunion and Rodrigues Islands), Comores archipelago (Mayotte) and Eparses atolls (Europa, Glorieuses, Juan de Nova and Tromelin), were sampled in 2007 and 2009 for environmental parameters and benthic diatoms studies. This preliminary note documents the nutrient concentrations [NO 3 − , NO 2 − , PO 4 − and Si(OH) 4 ] of coastal waters in diverse sites and examines the possible relationship between nutrient concentration and anthropogenic pressure. The pool of data is restricted, but the marine coastal environments of Réunion, Rodrigues and Mayotte exhibit, on average, higher levels of nutrient concentration, as compared to Eparses atolls, probably in relation to the degree of urbanisation. A project based on the study of benthic diatom assemblages will offer the opportunity to search for possible anthropogenic signatures.